Flies as vectors for Salmonella spp. and their control in pork butcheries in Kampala, Uganda – A contribution to improve public health - Heilmann, Martin (2016)
Synanthropic flies live close to humans and their animals, feed on their food and breed in faeces and other organic material. As such, they are known vectors for Salmonella spp., which are among the most common causes for foodborne diseases worldwide, especially in the developing world due to poorer sanitary conditions. Given that pork consumption in Uganda is rapidly increasing, while good food safety practices remain absent, this study aimed to assess the occurrence of Salmonella spp. in pork joints and to investigate the impact of insecticide-treated fence material on the number of flies in selected pork joints Kampala, Uganda.